A Data-Driven Framework to Address Gender Issues in Managing Flood Risks : Flood Risk Management Support Project for the City of Buenos Aires, Argentina - Kristof, Mariano Jordan; Ramirez, Maria Catalina; Pereira, Leda; Couvin, Sabrina (World Bank, Washington, DC, 2020)
This study contributes to the broader literature demonstrating the devastating impact of floods on the poor, particularly women, making it very difficult to move out of poverty. Research on flood impacts in low-income communities in Buenos Aires found that most first responders to floods are women and it is them who assume leadership roles in high-risk situations, despite the serious gender gaps in education and economic opportunities they face. They are also affected differently and more adversely than their male peers, bearing primary responsibility for restoring their family’s housing and livelihoods after the flood, and for household chores and care duties for children and older adults. The results of this analysis can help decision makers design gender-inclusive approaches for flood risk management, promoting and empowering women as positive agents of change. Gender gap analysis is essential to prevent existing inequalities from being maintained or accentuated as a part of the recovery process.